GABAB receptors in GtoPdb v.2021.2. (2021) - Bettler, Bernhard; Bowery, Norman G.; Cryan, John F.; Enna, Sam J.; Farb, David H.; Foestl, Wolfgang; Kaupmann, Klemens; Pin, Jean-Philippe
No abstract available